Election Polling and Late Swings in Vote Intentions - Pereira, Frederico Batista (2024)
Polls in the first round of Brazil's 2022 presidential election diverged from the official results, leading to criticisms that they made mistakes. This paper examines an alternative explanation: that actual changes in vote intentions occurred between the polls and election day. Although unpopular, this explanation finds theoretical support in the scholarship based on two main processes: strategic voting and delayed decision-making. Using an experiment conducted a week before the election, we show how undecided voters and voters for less competitive candidacies displayed high propensity to change their minds after watching campaign videos. We also use data from one of the last polls conducted before the election to develop models that identify voters most prone to late swings in vote choice and reallocate such votes to adjust vote estimates. The results suggest that late swings in vote intentions can be a more than plausible phenomenon in recent Brazilian elections.